2000
DOI: 10.1017/s0031182099006502
|View full text |Cite
|
Sign up to set email alerts
|

Impact of asymptomatic malaria parasitaemia on cognitive function and school achievement of schoolchildren in the Yemen Republic

Abstract: Asymptomatic malaria parasitaemia is prevalent among schoolchildren in many countries. The relationship between asymptomatic parasitaemia and children's cognitive functions was examined in a case control study and then in a natural experiment. A group (n = 445) of asymptomatic parasitaemic boys were compared with a group of non-parasitaemic boys (n = 142) matched for grade and school on their performance on a battery of cognitive tests. Two weeks later the parasitaemic children were re-screened and 150 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 127 publications
(224 reference statements)
1
55
0
1
Order By: Relevance
“…4 5 Malaria among school children has received increasing research attention over the last 10 years, with an expanding body of knowledge on the negative impacts that asymptomatic infection can have on health and education, as well as the deleterious effects of clinical attacks in this group. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] Nonetheless, there remains a paucity of evidence on the optimal control strategies in schoolchildren, and how these might vary between different malaria transmission settings. 20 21 Intermittent preventive treatment in schools has previously been shown to reduce malaria infections and anaemia and to improve sustained attention in an area of intense perennial transmission in western Kenya 12 but has not been evaluated in areas of seasonal transmission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 5 Malaria among school children has received increasing research attention over the last 10 years, with an expanding body of knowledge on the negative impacts that asymptomatic infection can have on health and education, as well as the deleterious effects of clinical attacks in this group. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] Nonetheless, there remains a paucity of evidence on the optimal control strategies in schoolchildren, and how these might vary between different malaria transmission settings. 20 21 Intermittent preventive treatment in schools has previously been shown to reduce malaria infections and anaemia and to improve sustained attention in an area of intense perennial transmission in western Kenya 12 but has not been evaluated in areas of seasonal transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics of children in control and intervention schools at baseline: November 2010 (classes[1][2][3][4][5][6] …”
mentioning
confidence: 99%
“…3 While the extant literature provides suggestive evidence of a malaria-cognition link, causation has not been credibly established. Several epidemiologic studies have demonstrated a relationship between malaria and cognitive outcomes in childhood (Al Serouri et al, 2000;Jukes et al, 2006;Boivin et al, 2007;John et al, 2007;Thuilliez et al, 2010). A single experimental study (Clarke et al, 2008) examines this link by looking at the impacts of malaria treatment on a test of sustained attention among 5-18 year olds in Western Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10%-28% of children who survive an episode of cerebral malaria develop neurological sequelae [1,3,4]. It has become increasingly recognized that cerebral malaria may cause persistent neurological and cognitive deficits that span a wide range of cognitive functions long after the infection has been successfully treated with antimalarial drugs, even in asymptomatic individuals [1][2][3][4][5][6][7][8]. Persistent deficiencies include attentional memory, learning and language impairments, visuospatial and motor deficits, and psychiatric disorders [3, 5, 6, 8 -15].…”
mentioning
confidence: 99%